Factors Associated with Glycemic Control among Type 2 Diabetic Patients in Primary Care Cluster, Muang Chainat District, Chainat Province - Wutthikitcharat, Wanida (Journal of Preventive Medicine Association of Thailand, 2023)
Objective: This study was aimed to explore associated factors of controllable blood sugar level among type 2 diabetic patients in Primary Care Cluster, Muang Chainat District, Chainat Province. Methods: It was an etiognostic exploratory cross-sectional study of 206 type 2 diabetic patients, selected by stratified random sampling. Data were collected by interviewing the sample group from June to August 2023 by using a set of questionnaire. The data were analyzed by using descriptive statistics and multiple logistic regression with statistic significant level at 0.05. Results: The results revealed that the appropriate fruits and vegetables consumption behavior and appropriate salt and sodium consumption behavior were significantly associated with good blood sugar control, with the adjusted OR 0.08 (95%CI 0.02, 0.36) and adjusted OR 0.26 (95%CI 0.09, 0.77), respectively (p<0.05). In contrast, the use of two antidiabetic medications (adjusted OR 3.93 [95%CI 1.52, 10.16]), three or more antidiabetic medications (adjusted OR 4.96 [95%CI 1.61, 15.28]), having experience of forgetting to take medication (adjusted OR 23.59 [95%CI 6.75, 82.42]) and LDL level ≥100 mg/dL (adjusted OR 4.04 [95%CI 1.28, 12.70]) were significantly associated with poor blood sugar control (HbA1c ≥7%), (p<0.05). Conclusion: To maintain normal blood sugar level (HbA1c <7%) in type 2 diabetes, suggested to emphasize on behavior modifications especially eating behavior and medication adherence.